2018
DOI: 10.3906/sag-1803-223
|View full text |Cite
|
Sign up to set email alerts
|

Ginger ( Zingiber officinale ) prevents severe damage to the lungs due to hyperoxia and inflammation

Abstract: Background/aim: Hyperoxia-and inflammation-induced lung injury is an important cause of the development of bronchopulmonary dysplasia (BPD) in premature infants. We aimed to ascertain the beneficial effects of ginger (Zingiber officinale) on rat pups exposed to hyperoxia and inflammation.Materials and methods: Thirty-six newborn Wistar rats were randomly divided into 3 groups as the hyperoxia (95% O 2 ) + lipopolysaccharide (LPS) group, the hyperoxia + LPS + ginger-treated group, and the control/no treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…Nonetheless, ginger has proven to relieve symptoms associated with COVID-19 infection such as chest pain. Ginger has proven to reduce chest pain and induce relaxation in airway smooth muscle, hindering airway resistance and inflammation as shown in Table 3 ( 166 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, ginger has proven to relieve symptoms associated with COVID-19 infection such as chest pain. Ginger has proven to reduce chest pain and induce relaxation in airway smooth muscle, hindering airway resistance and inflammation as shown in Table 3 ( 166 ).…”
Section: Methodsmentioning
confidence: 99%
“…The oily extract of the ginger rhizome was shown to reduce the LPS-induced IL-8 secretion suggesting that the ginger extract has anti-inflammatory effects on bronchial epithelial cells. 55 In another study on 36 newborn Wistar rats, ginger extract was shown to reduce the lung damage from severe damage due to hyperoxia and inflammation. 56 In the same study, it was seen that tissue TNF-α, IL-1β, and IL-6 concentrations were decreased in the animals treated with ginger in comparison to the placebo group.…”
Section: Ayurvedic Immunity-promoting Herbsmentioning
confidence: 98%
“…Oleoresin, gingerol, shogaol, and zingerone from ginger increased the percentage of CD3+CD4+ thus improving cellular and humoral immune response in HIV patients ( Tejasari, 2007 ). Ginger also alleviated bronchopulmonary dysplasia and inflammation induced by hyperoxia and intrauterine LPS in a chorioamnionitis rat model ( Cifci et al., 2018 ).…”
Section: Medicinal Plants With Pharmacological and Biological Action mentioning
confidence: 99%